Сказки: в 3 кн. : перевод с немецкого (Братья Гримм) - Гримм Вильгельм Карл (1993)
Экземпляры: ф.18 (1995) / Инвентарный номер: 37724 / Цена: / Сис.шифр: 84(4Гем)-4 / Авт.знак: Г 84 / ГРНТИ: 17.82.93 / ББК: 84(4Гем)-45